Slavery as a Form of Human Life (Vision of Antique Authors in the Light of the Ideas of the Russian Philosophers) - V. B. Aleksandrov (Управленческое консультирование, 2019)
In the article views of antique authors of human aspect of a phenomenon of slavery are considered. The author recognizes that the importance of a similar research is connected with existence of archetypic layers in the most various cultures causing reproduction of a phenomenon of slave model of the personality and corresponding to it behavior forms.The attention to three aspects in understanding of the bases of existence of the slave as special human type, recorded by antique authors is paid. It, first, slavery “under the law” according to which the captured captives are on sale in slavery. Secondly, this slavery caused by the human nature connected with ethnic origin on a formula “the barbarian and the slave by the concept nature identical”. Thirdly, this slavery in spiritual sense generated by the nature of activity in which the person is engaged. The types of activity forming the free person is for them philosophical reflection as disinterested search of the truth and also, according to Aristotle, political activity.Views of antique authors correspond in the article to views of the Russian religious philosophers proceeding from other paradigm of the activity basis of free existence implanted in Christian outlook. Its essence is that the aspiration to the truth which is implemented in occupations by philosophy has to be directed deep valuable installation, which sense in aspiration to connection of the person good luck.